Smell and taste disorders in pregnant women with COVID-19 - A. S. Kosovtseva; T. A. Bairova; L. V. Rychkova; E. A. Orlova; M. A. Khasnatinov; G. A. Danchinova; I. M. Mikhalevich; V. M. Polyakov; I. A. Cherevikova; N. A. Myasishchev; Zh. V. Prokhorova; L. I. Kolesnikova (Acta Biomedica Scientifica)
Background. Smell disorder is a recognized clinical symptom of COVID-19 infection. The problem of the loss of sense of smell in the structure of COVID-19 pathogenesis during pregnancy remains unresolved.   The aim of the study. To determine the sense of smell and taste in pregnant women with COVID-19, as well as to evaluate the relationship between the sense of smell and the number of SARS-CoV-2 genome equivalents in the nasopharyngeal secretion.   Material and methods. In the case-control study, 121 pregnant women participated: 40 of them were infected with COVID-19; 81 were not infected with COVID-19 earlier and at the time of the study. The survey was conducted in July 2021. Sense of smell was assessed using the Connecticut Chemosensory Clinical Research Center (CCCRC) olfactory test, which includes olfactory threshold determination and odor identification assessment. Taste was measured according to the O. Massarelli method. Viral load was calculated using a standardized method for determining the numberof SARS-CoV-2 RNA copies in 1 ml of nasopharyngeal secretion.   Results. The incidence of olfactory disorders (moderate / severe and anosmia) in pregnant women with COVID-19 is 62.5 % compared to 22.23 % among pregnant women who have never had COVID-19 (p = 0.002). No significant taste disorders were identified. The threshold value for the manifestation of olfactory disorders was 17794 RNA copies of the SARS-CoV-2 virus, which corresponds to the 37th threshold cycle (Ct).   Conclusion. During pregnancy in the acute phase of COVID-19, sense of smell is significantly impaired, but not sense of taste. Decreased sense of smell is associated with SARS-CoV-2 viral load.